Enhancing Senior High School Students' Critical Thinking in Economics Learning Through the Project-Based Learning Model - Selvita Eka Eviana Purba; Ari Data; Emirensiana Adha; Retno Hernawati; Erika Simanungkalit; Yeheskial Nggandung (AL-ISHLAH: Jurnal Pendidikan, 2025)
Critical thinking is essential in economics education, yet many senior high school students are still taught through memorization-focused methods, limiting the development of higher-order thinking skills. Project-Based Learning (PjBL) offers a potential alternative by engaging students in real-world, inquiry-based tasks. This quasi-experimental study employed a nonequivalent control group pretest–posttest design involving 71 senior high school students. The experimental group received instruction using the PjBL model, while the control group followed conventional teaching. Data were collected using a validated 20-item multiple-choice critical thinking test aligned with Bloom’s revised taxonomy (C4–C6). ANCOVA was used to analyze posttest differences, with pretest scores as covariates. Hedges’ g and normalized gain (N-gain) were calculated to assess effect magnitude and improvement. ANCOVA results revealed a statistically significant difference in posttest scores favoring the PjBL group (F = 5.686, p = .020), with a medium effect size (Partial Eta Squared = .078). The experimental group outperformed the control group with a mean posttest score of 67.86 versus 60.00. Hedges’ g was 0.522, and N-gain for the PjBL group (M = 0.558) exceeded that of the control group (M = 0.435). The findings suggest that PjBL is effective in enhancing students’ critical thinking in economics, particularly when projects are grounded in real-life contexts such as local inflation data. PjBL implementation requires structured planning, authentic tasks, and clear assessment criteria.